Nasa Balat ng Amerika - Asenjo, Genevieve L. (Likhaan: The Journal of Contemporary Philippine Literature; Vol 18 No 1 (2024): LIKHAAN 18 The Journal of Contemporary Philippine Literature, 2024)
“America is in the heart,” Carlos Bulosan said in 1946 when he narrated the experience of their generation of old Filipino migrant workers in California during the ’30s and ’40s of the twentieth century. “America is not the heart,” responded Elaine Castillo in 2018 when she narrated the lives of three generations of Filipino-American women in the Bay Area. Here’s a twenty first-century modern love story, “America Is on the Skin,” about the affair between a Black American soldier and a Filipina visiting Washington State, and how they navigate the silences and ghosts—remains and reminders of the continuing wars—present in their momentary union. This personal narrative offers a new and different plot in lyrical storytelling, beyond stereotypical and cliché characters, in a universal and enduring experience and human desire: safety, survival, and redemption.